Cerebrospinal fluid biomarkers for the differential diagnosis of Alzheimer's disease - Carolina A. Magalhães; Micheli Figueiró; Vanessa G. Fraga; Elvis C. Mateo; André A. S. F. Toledo; Maria das Graças Carvalho; Paulo Caramelli; Karina B. Gomes (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT Introduction: Several studies have been conducted in order to validate cerebrospinal fluid biomarkers for the diagnosis of Alzheimer's disease (AD), aiming primarily to facilitate the early diagnosis. Objective: To evaluate CSF biomarkers on patients with probable AD and the applicability of the international references values in this population. Methods: 46 individuals were recruited and classified as probable AD (n = 19), mild cognitive impairment (MCI) (n = 5) and other dementias (n = 22). The cerebrospinal fluid (CSF) biomarkers were measured using the INNOTEST kits for enzyme-linked immunosorbent assay (ELISA). Higher Tau protein values and lower Aβand Innotest Amyloid Tau Index (IATI) values were observed in AD group when compared with MCI; higher levels of Tau and phosphorylated Tau (P-Tau), and lower Aβand IATI values were observed in AD group when compared to patients with other dementias. No biomarker or IATI was able to distinguish between MCI and other dementias. The kappa index between biomarkers and the clinical diagnosis was regular to Tau and IATI, and weak to Aβand P-tau. Conclusion: The cut-off values for each biomarker that showed better combined sensibility and specificity differ from the reference values suggested by the manufacturer. The CSF biomarkers represent important resources that can help with the AD diagnosis, although the results interpretation must be made based on the analysis of the three analytes together. The cut-off values must be established to address the specificities and characteristics of each population.